Margin squeeze in fixed-network telephony markets: competitive or anticompetitive? - Wolfgang Briglauer; Georg Götz; Anton Schwarz (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
This paper looks at the effects of different forms of wholesale and retail regulation on retail competition in fixed network telephony markets. We explicitly model two asymmetries between the incumbent operator and the entrant: (i) While the incumbent has zero marginal costs, the entrant has the wholesale access charge as (positive) marginal costs; (ii) While the incumbent is setting a two-part tariff at the retail level (fixed fee and calls price), the entrant can only set a linear price for calls. Competition from other infrastructures such as mobile telephony or cable is modelled as an outside opportunity for consumers. We find that a horizontally differentiated entrant with market power may be subject to a margin squeeze due to double marginalization but will never be completely foreclosed. Entrants without market power might be subject to a margin squeeze if the wholesale access price is set at average costs and competitive pressure from other infrastructures increases. We argue that a wholesale price regulation at average costs is not optimal in such a situation and discuss retail minus and deregulation as potential alternatives.
Keywords: L12; L41; L42; L50; L96; 330; access regulation; foreclosure; margin squeeze; telecommunications; fixed networks